2005
DOI: 10.1523/jneurosci.0365-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Triggers Reactive/Inflammatory Processes in Astrocytes and Is Upregulated in Aging and Alzheimer's Models

Abstract: Astrocyte reactivity (i.e., activation) and associated neuroinflammation are increasingly thought to contribute to neurodegenerative disease. However, the mechanisms that trigger astrocyte activation are poorly understood. Here, we studied the Ca 2ϩ -dependent phosphatase calcineurin, which regulates inflammatory signaling pathways in immune cells, for a role in astrogliosis and brain neuroinflammation. Adenoviral transfer of activated calcineurin to primary rat hippocampal cultures resulted in pronounced thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
216
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(232 citation statements)
references
References 62 publications
13
216
3
Order By: Relevance
“…The involvement of CaN in the neurodegenerative process and memory impairment in AD and PRE remains a controversial issue (Wang et al, 1999;Norris et al, 2005;Biasini et al, 2006;Dineley et al, 2007). In a previous study we demonstrated that Ab and PrP peptides trigger a caspase-3-dependent apoptotic neuronal death pathway, involving CaN and cyt c release from mitochondria (Agostinho and Oliveira, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…The involvement of CaN in the neurodegenerative process and memory impairment in AD and PRE remains a controversial issue (Wang et al, 1999;Norris et al, 2005;Biasini et al, 2006;Dineley et al, 2007). In a previous study we demonstrated that Ab and PrP peptides trigger a caspase-3-dependent apoptotic neuronal death pathway, involving CaN and cyt c release from mitochondria (Agostinho and Oliveira, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…37 Ab species, particularly oligomers, can activate both astrocytes and microglia. 38,39 Recently, genetic data 40e44 corroborated by experimental studies 45e49 have directly implicated microglia in the pathogenesis of AD through mechanisms that involve either Ab phagocytosis or the secretion of proinflammatory cytokines. Similarly, reactive Figure 4 The association between SMI312 þ dystrophic neurites per plaque and symptom duration is stronger at initial stages.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the activation phenotype of both astrocytes and microglial cells was reported to be largely mediated through the calcineurin-nuclear factor of activated T cells pathway. 48,49 Fibrillar and particularly oligomeric A␤ can aberrantly activate this molecular signaling pathway in glial cells 48,50 and neurons, causing the morphological triad of dystrophic neurites, dendritic simplification, and loss of dendritic spines, subsequently leading to cognitive impairment. [51][52][53] More important, Food and Drug Administration-approved and available calcineurin inhibitors, Figure 7.…”
Section: Diagnostic and Therapeutic Implicationsmentioning
confidence: 99%